Pengaruh Ketidaknyamanan Kerja terhadap Kinerja Karyawan: Eksplorasi Peran Modal Psikologis (Studi Empiris pada Hotel Berbintang) - Indrayani, I Gusti Ayu Putu Wita (Jurnal Ilmiah Pariwisata; Vol 28 No 2 (2023): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v28i2.1700, 2023)
Structural changes that occurred in the tourism sector during the global COVID-19 crisis have the potential to have a negative psychological impact on hotel employees. Job insecurity, which refers to the potential for loss of continuity of work, has implications for a decrease in employee performance. This study aims to explore the role of employee psychological capital (self-efficacy, optimism, hope, and resilience) as a moderator in the relationship between job insecurity and performance. To answer the research objectives, this study used a quantitative method with a variant-based approach through partial least squares. The population in this study is all millennial employees at star hotels in Bali. The findings in this study indicate that psychological capital is proven to be able to moderate the effect of job insecurity on the performance of millennial employees. The individual dimension plays a key role in determining competitive advantage in the hospitality industry. This study shows that under conditions of job uncertainty, employees with high psychological capital are more successful at coping with stress and show performance levels that meet standards. Therefore, practical strategies to increase employees' positive psychological resources must be developed to help them adapt to business situations full of volatility and vulnerability. Keywords: Conservation of Resources Theory, Hotel,  Millennial, Work Behavior